Analysis of broadband absorbing non magnetic materials / Arba'iah Inn - Inn, Arba'iah (1995)
An analytical approach, through the lossy transtnission line technique is used to design Wave Absorbing Non-Magnetic Materials (WANMMs). Tliese WANMMs are made of several diclecti ie layers, usually on top of a conducting plane. The total absorption of the electromagnetic energy is done in the last lossy layer. Other layers are used to match the wave impedance of the WANMM to tliat of the incidence media for the nonnal incidence only at different microwave frequencies. The approach is easy, practical and flexible, allowing the design of WANMM for specific applications such as Radar Absorbing Materials (RAMs) and Wireless Local Area Networks (AVLANs). A wide range of frequencies is considered to maintain a minimum range of reflection.